Comparison of several different neutralisations to a bauxite refinery residue: Potential effectiveness environmental ameliorants. (May 2015) - Clark, M.W.; Johnston, M.; Reichelt-Brushett, A.J.
Graphical abstract: Highlights: Different neutralisation techniques affect if and how alkalinity precipitation occurs. Different alkalinity; precipitations affect surface chemistry, and metal removal. P removal is greatly affected by Ca and Mg availability. Basecon™ and hybrid material have greater metal binding capacities, and leach stability. Hybrid neutralised materials provide some additional benefits through CO2 sequestration. Abstract: Bauxite refinery residues (BRR) remain the single largest environmental problem for the alumina industry, because of the fine-grained nature (>90% at <10 μm), high pH (>13), high sodicity (>50 g/kg), and high alkalinity (typically ≈30 g/kg as equivalent CaCO3 ). However, neutralisation of BRR provides a geochemically engineered solution, with potential re-use options. Hence, we compare the geochemistry of 4 BRRs: the un-neutralised raw red mud (UNRM), a CO2 -neutralised red mud (CNRM), a Basecon™-neutralised (Basecon™) red mud, and a CO2 -neutralisation followed by a Basecon™-neutralisation (Hybrid) material from a common source for reuse potential. Compositional changes, including acid neutralising capacity, trace-metal and phosphorous binding capacities, and toxicity leaching characteristics (TCLP) show that different neutralisations produce two geochemically distinct solids, those without alkalinity precipitation, and those with solid alkalinity. From the work completed, both Basecon™-neutralised and Hybrid materials have a significantly higher reuse potential for environmental remediation programs, such as acid rock drainage neutralisations, wastewater treatment, and/or artificial soil construction.